Multistakeholder networks promoting cocoa farming and silvopastoral livestock in Caquetá, Colombia - Guáqueta Solórzan, Victoria; Ayazo Berrocal, Roger; Vanegas Cubillos, Martha (2024)
The department of Caquetá, in the Colombian Amazon, has become a focal point for various national and international institutions aiming to promote sustainable production systems that contribute to the reduction of deforestation, climate change mitigation and adaptation, and peacebuilding. This institutional interest is rooted in the region’s history of violence, cultivation of crops for illicit purposes, and a significant advance in the arc of deforestation towards the Amazon region, one of the most important biodiversity hotspots in the world.